2015
DOI: 10.1111/gcb.12993
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of temporal changes in temperate forest plant diversity vary across spatial scales

Abstract: Global biodiversity is affected by numerous environmental drivers. Yet, the extent to which global environmental changes contribute to changes in local diversity is poorly understood. We investigated biodiversity changes in a meta-analysis of 39 resurvey studies in European temperate forests (3988 vegetation records in total, 17-75 years between the two surveys) by assessing the importance of (i) coarse-resolution (i.e., among sites) vs. fine-resolution (i.e., within sites) environmental differences and (ii) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
160
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(175 citation statements)
references
References 48 publications
13
160
2
Order By: Relevance
“…; Bernhardt‐Römermann et al. ). Our results for vascular plants were less clear, but not inconsistent with the hypothesis of N deposition as a driver of vegetation change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Bernhardt‐Römermann et al. ). Our results for vascular plants were less clear, but not inconsistent with the hypothesis of N deposition as a driver of vegetation change.…”
Section: Discussionmentioning
confidence: 99%
“…; Wiegmann & Waller ; Bernhardt‐Römermann et al. ). In communities that have not undergone major land‐use transitions, dominant global change factors include climate change (especially warming) and atmospheric N deposition (Field et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Bernhardt‐Roemermann et al. ), and consistent changes across scales (e.g., Eskildsen et al. , Harrison et al.…”
Section: Introductionmentioning
confidence: 95%
“…Recent examples of studies that resurvey legacy data are found across various ecosystems, ranging from mountain tops (Wipf, Stöckli, Herz, & Rixen, ), over forests (Naaf & Kolk, ), moorlands (Britton, Hester, Hewison, Potts, & Ross, ) and hedgerows (Litza & Diekmann, ), to prairies (Alstad et al., ) and grasslands (Gillet, Mauchamp, Badot, & Mouly, ; Stevens et al., ). Besides these single region and single system studies, more and more multi‐region and/or multi‐system studies are emerging (Bernhardt‐Römermann et al., ; De Frenne et al., ). Combining resurveys allows us to check for the generality of community change (Vellend, Baeten et al., ) and helps to better understand the relative importance of, and interactions between, the different drivers of change (Verheyen et al., ).…”
Section: Introductionmentioning
confidence: 99%